Improved survival for severely injured patients receiving massive transfusion at US teaching hospitals: A nationwide analysis. Issue 5 (6th May 2023) - Ramsey, Walter A.; O'Neil, Christopher F.; Fils, Aaron J.; Botero-Fonnegra, Cristina; Saberi, Rebecca A.; Gilna, Gareth P.; Pizano, Louis R.; Parker, Brandon M.; Proctor, Kenneth G.; Schulman, Carl I.; Namias, Nicholas; Meizoso, Jonathan P.
Abstract : This review of the 2019 TQIP dataset demonstrates that #teaching trauma centers outperform #nonteaching centers in the treatment of patients requiring massive transfusion. Abstract : BACKGROUND: Previous studies have shown improved survival for patients treated at American College of Surgeons (ACS)–verified level I trauma centers compared with level II, level III, and undesignated centers. This mortality difference is more pronounced in severely injured patients. However, a survival benefit for severely injured trauma patients has not been established at teaching institutions compared with nonteaching centers. Because massive transfusion (MT) is associated with high mortality, we hypothesize that patients receiving MT have lower mortality at teaching hospitals than at nonteaching hospitals. METHODS: All adult ACS Trauma Quality Improvement Program–eligible patients who underwent MT, defined as >10 U of packed red blood cells in the first 4 hours after arrival, in the 2019 ACS Trauma Quality Programs participant use file were eligible. Patients with severe head injury (head Abbreviated Injury Scale score, ≥3), prehospital cardiac arrest, and interhospital transfers were excluded. Logistic regression models were used to assess the effects of trauma center hospital teaching status on the adjusted odds of 3-hour, 6-hour, and 24-hour mortality. RESULTS: A total of 1, 849 patients received MT (81% male; median Injury Severity Score, 26 [18–35]), 72% were admitted to level I trauma centers, and 28% were admitted to level II centers. Overall hospital mortality was 41%; 17% of patients died in 3 hours, 25% in 6 hours, and 33% in 24 hours. Teaching hospitals were associated with decreased 3-hour (odds ratio [OR], 0.45; 95% confidence interval [CI], 0.27–0.75), 6-hour (OR, 0.37; 95% CI, 0.24–0.56), 24-hour (OR, 0.50; 95% CI, 0.34–0.75), and overall mortality (OR, 0.66; 95% CI, 0.44–0.98), compared with nonteaching hospitals, controlling for sex, age, heart rate, injury severity, injury mechanism, and trauma center verification level. CONCLUSION: Severely injured patients requiring MT experience significantly lower mortality at teaching hospitals compared with nonteaching hospitals, independently of trauma center verification level. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :